SYNTHESIS OF 1,4-BENZODIAZEPINE THROUGH PHOTOCHEMICAL REACTION OF 3-PHENYL-3,6-DIHYDRO-[1,2]DIOXINE WITH ETHYLENDIAMINE - Muhammad Nazar (Chimica Didactica Acta, 2013)
Synthesis of 1,4-Benzodiazepine via reaction of ethylendiamine with 3-phenyl-1,2-dioxine has been carried out. The first step of this experiment was conversion of triphenyl phosphine to triphenyl metyl phosphine iodide which was then used to form phenyl butadiene from cinnamaldehyde. The synthesis of phenyl dioxine was done via photochemical reaction of phenyl butadiene with oxygen gas in the presence of tetraphenyl posphene. The coupling reaction between phenyl phosphine and ethylendiamine was carried out under atmospheric pressure at room temperature. All steps of these reactions were confirmed using TLC with appropriate eluents and the resulting compounds were purified using column chromatography. In addition, all products structure including phenyl dioxine and 1,4-benzodiazepine were determined using HNMR.